Model Of Management Information System For Village-Owned Enterprises In Increasing Regional Per Capita In Sambas District - Farah Devi Andriani; Sri Haryaningsih; Elyta; Mohammad Nabil Almunawar (International Journal of Economics, Business and Innovation Research, 2023)
This study aims to see how the Management Information System for Village-Owned Enterprises in Improving Regional Per Capita in Sambas Regency. Sambas Regency is one of the regencies directly adjacent to Malaysia. At the level of Village-Owned Enterprises, it is still relatively low in increasing regional per capita. The method used is a qualitative method with a literature study. The results of this study look through the SWOT Analysis in the Strategy that will be carried out to empower and activate VOEs in improving the economy and the Village-Owned Enterprise Management Information System Model.